Functionalization of cellular membranes with DNA nanotechnology - Schönit, Andreas; Cavalcanti-Adam, Elisabetta A.; Göpfrich, Kerstin (Trends in biotechnology, 2021)
Due to its versatility and programmability, DNA nanotechnology has greatly expanded the experimental toolbox for biomedical research. Recent advances allow reliable and efficient functionalization of cellular plasma membranes with a variety of synthetic DNA constructs, ranging from single strands to complex 3D DNA origami. The scope for applications, which probe biophysical parameters or equip cells with novel functions, is rapidly increasing. These applications extend from programmed cellular connectivity and tissue engineering to molecular force measurements, controlled receptor-ligand interactions, membrane-anchored biosensors, and artificial transmembrane structures. Here, we give guidance on different strategies to functionalize cellular membranes with DNA nanotechnology and summarize current trends employing membrane-anchored DNA as a tool in biophysics, cell biology, and synthetic biology.